A matter of style: looking at L2 teachers' teaching styles from the perspective of learning styles - Tavares, Maria da Glória Guará (2004)
The present study aims at investigating L2 teachers’ teaching styles from the perspective of learning styles to identify the learning styles which tend to be most favored by foreign language teachers, the relationship between teachers’ teaching styles and their own learning styles, students’ attitudes towards discussing learning preferences in the classroom, and difficulties teachers face when trying to develop a balanced teaching style. The data for the present study were collected at the Extracurricular Language Courses offered by Universidade Federal de Santa Catarina (UFSC), from April, 16th to July 4th , 2002. Eight teachers of English as a foreign language – two at the beginning level, two of the pre-intermediate level, two of the intermediate level, and two of the high-intermediate level – were observed for the purpose of investigating their teaching styles from the perspective of learning styles. Out of the eight teachers, six were observed for three classes. The other two were observed for six classes, took part in an instructional program, and were required to accomplish two tasks. Task one consisted of trying to approach students’ learning styles and task two consisted of trying to develop a balanced teaching style. For the data collection, seven instruments were used: (1) classroom observation, (2) audio recordings, (3) one instrument for assessing teaching styles, (4) one instrument for assessing learning styles, (5) one questionnaire for assessing students’ attitudes, (6) a reflective session, and (7) a semi-guided interview with teachers. The framework for data analysis was the Myers and Briggs Learning Style Model (1987). Results indicate that (1) extraverts, feelers, perceivers and kinesthetic tend to be the learning styles most favored, (2) there seems to be a correlation between teachers’ teaching styles and their own learning styles, (3) students present a positive attitude towards teachers’ attempts to discuss learning styles, and (4) teachers face two main difficulties when trying to develop a balanced teaching style: lack of time for planning their classes and lack of knowledge of learning style theories.